Ideal Work Practices for Students in Distance Universities to Improve the Quality of Education and Career Preparation: a case study of the Taxation study program - Syafiqoh Nurhayati; Dedy Juniadi; Erman Arif (Eduvest - Journal of Universal Studies, 2024)
Higher education plays an important role in preparing students for the workforce.  This article looks at modelling ideal work practices for students with a focus on improving the quality of their education and career preparation. The main objective is to build a conceptual and operational framework to gain a solid basis for investigating the main factors related to the ideal work practice model that leads to student satisfaction academically. The final result of this proposal is also expected to be able to produce variables in order to make online learning better meet the needs of students. For this reason, this proposal will develop an operational model to be tested by referring to the conception of the Unified Theory of Acceptance and Use of Technology (UTAUT). In the end, as the final result, this study is expected to give birth to an integrated idea, how to implement more effective work practices in the future seen from the student side. Then, what should colleges prepare and do? To achieve that, this study will use the Mixed Methods. Precisely exploratory design (exploratory design). That is, the study was carried out with a qualitative approach first. Then proceed with a quantitative approach. The end result of this qualitative process will produce operational thinking shells that can be continued the quantitative analysis process. The results of this study are expected to contribute to the development of concepts and literature on ideal work practices in online learning seen through a combination of UTAUT conceptions.